Vestibular Function After Cochlear Implantation in Partial Deafness Treatment - Sosna-Duranowska, Magdalena; Tacikowska, Grazyna; Gos, Elzbieta; Krupa, Anna; Skarzynski, Piotr Henryk; Skarzynski, Henryk (Frontiers in Neurology, 2021)
Introduction: Cochlear implantation is a fully accepted method of treating individuals with profound hearing loss. Since the indications for cochlear implantation have broadened and include patients with low-frequency residual hearing, single-sided deafness, or an already implanted ear (meaning bilateral cochlear implantation), the emphasis now needs to be on vestibular protection. Materials and Methods: The research group was made up of 107 patients operated on in the otorhinolaryngosurgery department: 59 females and 48 males, aged 10.4–80.2 years (M = 44.4; SD = 18.4) with hearing loss lasting from 1.4 to 56 years (M = 22.7; SD = 13.5). The patients underwent cVEMP, oVEMP, a caloric test, and vHIT assessment preoperatively, and, postoperatively, cVEMP and oVEMP at 1–3 months and a caloric test and vHIT at 4–6 months. Results: After cochlear implantation, there was postoperative loss of cVEMP in 19.2% of the patients, oVEMP in 17.4%, reduction of caloric response in 11.6%, and postoperative destruction of the lateral, anterior, and posterior semicircular canal as measured with vHIT in 7.1, 3.9, and 4% respectively. Conclusions: Hearing preservation techniques in cochlear implantation are connected with vestibular protection, but the risk of vestibular damage in never totally eliminated. The vestibular preservation is associated with hearing preservation and the relation is statistically significant. Informed consent for cochlear implantation must include information about possible vestibular damage. Since the risk of vestibular damage is appreciable, preoperative otoneurological diagnostics need to be conducted in the following situations: qualification for a second implant, after otosurgery (especially if the opposite ear is to be implanted), having a history of vestibular complaints, and when there are no strict audiological or anatomical indications on which side to operate.